What kind of preference maximization does the weak axiom of revealed non-inferiority characterize? - Michele Lombardi (Queen Mary University of London, Department of Economics, 2007)
A multi-valued choice is weak justified if no chosen alternative is dominated by any other obtainable alternative, and for each discarded alternative there is some chosen alternative which dominates it. This definition allows us to build a connection between the behavioral property expressed by the weak axiom of revealed non-inferiority and a weak notion of rationality. Our notion of rationaity is weaker than that characterized by the weak axiom of revealed preference.
Keywords: D0; 330; Weak axiom of revealed non-inferiority; Entscheidungstheorie